Project management : systems, principles, and applications - Badiru, Adedeji Bodunde, 1952- (Industrial innovation series., 2012)
"Preface A systems view of the world is the premise of this book. The book's emphasis is the belief that there is a better way (systems approach) to accomplishing goals and objectives in managing projects. Project management is the process of managing, allocating, and timing resources to achieve a given goal in an efficient and expeditious manner. The objectives that constitute the specified goal may be in terms of time, cost, or technical results. A project can be simple or complex. In each case, proven project management processes must be followed with a world systems view of the project environment. While on-the-job training is possible for many of the project management requirements, rigorous and formal training must be utilized. Consequently, project management textbooks are of high utility. This textbook fills the void that exists in the availability of project management textbooks. It covers contemporary tools and techniques of project management from an established pedagogical perspective. It is designed to serve as a textbook in colleges and universities for project management and related courses at the senior undergraduate and first-year graduate levels. Specific programs that will be of interest in the book include industrial engineering, systems engineering, construction engineering, operations research, engineering management, business management, general management, business administration, mechanical engineering, civil engineering, production management, industrial management, and operations management. The book contains ample graphical representations to clarify the concepts and techniques presented. The end-of-chapter exercises help to reinforce the topics covered in each chapter. The project systems approach presented in the book is needed"--